Detection of Digital Law Issues and Implication for Good Governance Policy in Indonesia - Awaludin Marwan; Diana Odier-Contreras Garduño; Fiammetta Bonfigli (Administrative Law Departement Faculty of Law Universitas Sebelas Mare, 2022)
The concept of good governance is essential to be utilized to analyze updating digital law and society. However, at the practical level, it can still be seen the lack of implementation of the principle of properness, transparency, effectiveness, accountability, participation, and human rights by the government to respond to the economic growth and criminal trend within the digital era. This study discusses good governance as a concept that can be used to analyze digital law and society. Especially in the cybercrime and e-businesses in Indonesia, the concept of good governance may utilize the social impact. This study uses socio-legal research, which combines interviews and literature review. This article will start to discuss the relevance of the study of good governance, digital law, and society in Indonesia's social and judicial context with the Electronic Information Transaction Law. This study concludes that during the growth of the digital economy, Indonesia has suffered from cyber-attacks, scams, phishing, malware injection, etc., which may need more extraordinary law enforcement. At the same time, the increasing number of e-commerce, fintech, social media, digital start-up, etc., need support from proper facilitation by the government. Good governance may provide a tool to cover the objective and balance its outcomes in the digital era.